2004
DOI: 10.1097/00005537-200410000-00019
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ascorbic Acid on Oxidative System and Transient Evoked Otoacoustic Emissions in Rabbits Exposed to Noise

Abstract: Ascorbic acid treatment inhibited both lipid peroxidation and oxidative damage of proteins in rabbits exposed to noise. The study data suggest, at least, that oxidative status should be included in the physiopathology of noise-induced hearing loss; in addition, a brief application of ascorbic acid before noise exposure appeared to play a protective role for cochlea.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 14 publications
0
17
0
Order By: Relevance
“…As an antioxidant capable of working in both aqueous and nonaqueous environment (22), AA is a good choice of treatment in cases like essential hypertension where an increased free radical production or reduced antioxidant (27,28) level plays an important role in the pathogenesis as well as in long-term complications (29,30). In this study, treatment with ascorbic acid produced a significant reduction in systolic blood pressure in the SHR.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…As an antioxidant capable of working in both aqueous and nonaqueous environment (22), AA is a good choice of treatment in cases like essential hypertension where an increased free radical production or reduced antioxidant (27,28) level plays an important role in the pathogenesis as well as in long-term complications (29,30). In this study, treatment with ascorbic acid produced a significant reduction in systolic blood pressure in the SHR.…”
Section: Discussionmentioning
confidence: 59%
“…Ascorbic acid (AA), a water soluble antioxidant, provides a strong defense against free radical activity, also has been reported to reduce lipid peroxidation in experimental studies (20,21), and can exert its antioxidant properties in both aqueous and nonaqueous environments (22). Furthermore, AA can potentiate the activity of vitamin E by sparing it, and by further reducing it from the oxidized form (23).…”
Section: Introductionmentioning
confidence: 99%
“…Other antioxidants that can potentially play a protective role against noise-induced cochlear trauma include ginseng [172], co-enzyme Q10 [177], as well as several vitamins, such as vitamin A [178], vitamin C [179, 180], vitamin E [181, 182], and vitamin B12 [183]. Studies in animals showed a protective benefit from combination antioxidant treatment, such as magnesium and vitamin A, C, and E [184], possibly due to synergistic effects [185187], These studies were mainly performed in animals or in small groups of humans and the results should be considered preliminary.…”
Section: Pharmacological Treatmentsmentioning
confidence: 99%
“…That antioxidant agents effectively reduce sensory cell death and NIHL has now been well demonstrated in animal studies using a variety of antioxidant agents, such as GSH/ glutathione monoethyl ester (GSHE) (Ohinata et al, 2000b;Kopke et al, 2002;Hight et al, 2003;Miller et al, 2003a), resveratrol (Seidman et al, 2003), allopurinol (Seidman et al, 1993;Cassandro et al, 2003), superoxide dismutase-polyethylene glycol (Seidman et al, 1993), U74389F (a lazaroid drug which inhibits lipid peroxidation and scavenges free radicals) (Quirk et al, 1994), and R-phenylisopropyladenosine (R-PIA) (Hu et al, 1997;Hight et al, 2003). Small protective effects of individual (or combined) dietary antioxidant nutrients are also well described for insults to the inner ear including noise, drugs, and age (Chole and Quick, 1976;Lohle, 1980Lohle, ,1985Romeo, 1985;Biesalski et al, 1990;Lopez-Gonzalez et al, 2000;Seidman, 2000;Bertolaso et al, 2001;Pasqualetti and Rijli, 2001;Teranishi et al, 2001;Rabinowitz et al, 2002;Hou et al, 2003;Derekoy et al, 2004;Kalkanis et al, 2004;Weijl et al, 2004;Ahn et al, 2005;McFadden et al, 2005;Yamashita et al, 2005a).…”
Section: Enhancing Antioxidant Defense Attenuates Nihlmentioning
confidence: 99%